2018
DOI: 10.3390/rs10050765
|View full text |Cite
|
Sign up to set email alerts
|

Centimetric Accuracy in Snow Depth Using Unmanned Aerial System Photogrammetry and a MultiStation

Abstract: Performing two independent surveys in 2016 and 2017 over a flat sample plot (6700 m 2 ), we compare snow-depth measurements from Unmanned-Aerial-System (UAS) photogrammetry and from a new high-resolution laser-scanning device (MultiStation) with manual probing, the standard technique used by operational services around the world. While previous comparisons already used laser scanners, we tested for the first time a MultiStation, which has a different measurement principle and is thus capable of millimetric acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
56
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 62 publications
(88 reference statements)
10
56
1
1
Order By: Relevance
“…In addition, airborne laser scanning (ALS) and terrestrial laser scanning (TLS) technologies have been applied as the preferred methods to obtain HS data [3,[26][27][28][29][30][31][32][33]. Moreover, tachymetry [28], ground-penetrating radar (GPR) [34,35], and time-lapse photography [36,37] have been used.The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, airborne laser scanning (ALS) and terrestrial laser scanning (TLS) technologies have been applied as the preferred methods to obtain HS data [3,[26][27][28][29][30][31][32][33]. Moreover, tachymetry [28], ground-penetrating radar (GPR) [34,35], and time-lapse photography [36,37] have been used.The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46].…”
mentioning
confidence: 99%
“…Moreover, tachymetry [28], ground-penetrating radar (GPR) [34,35], and time-lapse photography [36,37] have been used.The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46]. Also, different camera sensors that record data in various parts of the electromagnetic spectrum, such as visible (350-680 nm) and near infrared (NIR) (in different ranges (>700 and >830 nm)), have been evaluated [10,43,44].…”
mentioning
confidence: 99%
“…Like lidar and digital photogrammetry methods, SFM‐derived snow depth maps are computed by differencing two coregistered elevation models acquired for snow‐covered (snow‐on) and snow‐free (snow‐off) conditions. Reported snow depth root mean squared errors (RMSEs) using UAVs in alpine areas typically range between 7 and 30 cm (Adams et al, ; Avanzi et al, ; Bühler et al, ; de Michele et al, ; Harder et al, ; Vander Jagt et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the SFM‐derived elevation models for snow depth mapping generally depends on field site conditions, survey design, and the SFM software. These aspects can include the snowpack conditions (e.g., the presence of fresh snow or ice; Gindraux et al, ; Fernandes et al, ; Bühler et al, ; Cimoli et al, ; Vander Jagt et al, ; de Michele et al, ), terrain conditions (e.g., hilly or flat; Cimoli et al, ; Avanzi et al, ), lighting conditions (i.e., presence of shadows; e.g., zenith angle of the sun and cloud coverage; Goetz et al, ; Nolan et al, ; Cimoli et al, ; Harder et al, ; Bühler, Adams, Stoffel, et al, ; Gindraux et al, ), characteristics of the UAV survey (e.g., flying height, image overlap, and distribution of ground control; Goetz et al, ; James et al, ; Tonkin et al, ; Gindraux et al, ), and the SFM software processing (e.g., settings for sparse and dense point cloud quality; Cimoli et al, ; Hendrickx et al, ; Gindraux et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation